O ensino da língua adicional através de uma proposta de letramento - Hansen, Jaqueline (Universidade do Vale do Rio dos Sinos, 2016)
This paper aims to show the reality of additional language teaching from a proposal of literacy for future implementation in a class of 2nd year of Elementary School in a bilingual educational context. This work also discusses the concepts of social literacy, additional language and organizational characteristics of the bilingual curriculum. Researchers and authors of the area as Leffa and Irala (2014), and Schlatter and Garcez (2012), Dias (2015) among others, as well as the National Curriculum Parameters provided the theoretical basis for the research developed. After reflection on the different concepts studied, a proposal of a cooking class was planned for future development, to reflect on the possibilities of developing a proposal for social literacy in an additional language class.
Keywords: Língua adicional; Letramento; Currículo bilíngue; Aula de culinária; Additional language; Literacy; Bilingual curriculum; Cooking class